"I Was Not Willing to Risk my Hajj": Information Coping Strategies of Hajj Pilgrims. Issue 1 (1st June 2020) - Caidi, Nadia
Abstract: Information phenomena and behaviors underlie every aspect of contemporary life, including spiritual/religious experiences. Pilgrimage as an information context provides insights into the nature of information and knowledge in the lives of individuals undergoing such transformational experiences. Findings based on interviews with twelve Hajj pilgrims suggest that their information practices are varied and transcend both individual (cognitive, affective) and social processes (through shared imaginaries and a wide network of people and resources). As pilgrims prepare for and complete the rituals, then return home, they make use of a range of coping strategies from triangulation and validation to information avoidance. Examining the information strategies of Hajj pilgrims provide us with insights into their processes of negotiating meaning in shifting and unknown contexts.